Case study on AgFeed industries. - Wu, Jia Hui. (2012)
AgFeed Industries, Inc. is an international agribusiness with operations in the United States and China. It was founded in 1995 by four Chinese businessmen who saw great potential in the feed business in China before a series of events took place and changed the key management of the company. The business first started with Dr. Li Song Yan leading the team to set up their base in Nanchang. All the founders have vast experience in the agricultural sector and they were geared to develop their business in the feed industry. Over the years, AgFeed took up many acquisition projects in order to expand their production capacity. The team developed the feed unit and integrated vertically into the hog production segment. In 2007, the company successfully secured listing on the NASDAQ stock market. AgFeed then recognized the need for them to incorporate new technologies into their production system. With this in mind, AgFeed launched a joint venture with M2P2, a US leading hog production company, in 2009. The joint venture benefited both parties and in 2010, AgFeed proceed to acquire M2P2. As part of the acquisition agreement, John Stadler, Chairman of M2P2, joined AgFeed’s Board of Directors. Subsequently, AgFeed restructured its management team in order to better manage its business units.